Gambaran Penilaian Kinerja Karyawan di RSUD Mohammad Natsir Solok Tahun 2022 - Miftahul Hidayah; Erpidawati Erpidawati; Silvia Adi Putri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
Employee performance is less effective because there are employees who don't arrive on time, there are employees who are not in place during working hours, and there is poor communication between employees in the working relationship. The purpose of this study was to describe the quality, quantity, timeliness and work effectiveness of the employees of RSUD Mohammad Natsir Solok. The type of research used is quantitative with a descriptive approach. The population in this study were all employees and the sample obtained using the Slovin formula, namely 80 respondents with a sample collection technique namely quota sampling and the data analysis technique used was univariate data analysis. The results of the study on the description of the quality, quantity, timeliness and work effectiveness of the employees of RSUD Mohammad Natsir Solok is high, although some are still low. For this reason, suggestions that can be submitted are in order to maintain and further improve the performance of the employees of RSUD Mohammad Natsir Solok both in terms of indicators of quality, quantity, timeliness and work effectiveness of employees.